National Survey of Health Attitudes, (United States), 2015 - Chandra, Anita ([Verlag nicht ermittelbar], 2020)
Since 2013, the Robert Wood Johnson Foundation (RWJF) has led the development of a pioneering national action framework to advance a "culture that enables all in our diverse society to lead healthier lives now and for generations to come." Accomplishing these principles requires a national paradigm shift from a traditionally disease and health care-centric view of health toward one that focuses on well-being. Recognizing that paradigm shifts require intentional actions, RWJF worked with RAND researchers to design an actionable path to fulfill the Culture of Health (CoH) vision. A central piece of this work is the development of measures to assess constructs underlying a CoH. The National Survey of Health Attitudes is a survey that RWJF and RAND analysts developed and conducted as part of the foundation's CoH strategic framework. The foundation undertook this survey to measure key constructs that could not be measured in other data sources. Thus, the survey was not meant to capture the full action framework that informs CoH, but rather just selected measure areas. The questions in this survey primarily addressed the action area: making health a shared value. The survey covers a variety of topics, including views regarding what factors influence health, such as the notion of health interdependence (peer, family, neighborhood, and workplace drivers of health), values related to national and community investment for health and well-being; behaviors around health and well-being, including civic engagement on behalf of health, and the role of community engagement and sense of community in relation to health attitudes and values.